Molecular signatures of T-cell inhibition in HIV-1 infection - Larsson, M.; Shankar, E.M.; Che, K.F.; Saeldi, A.; Ellegard, R.; Barathan, M.; Velu, V.; Kamarulzaman, A. (BioMed Central, 2013)
Cellular immune responses play a crucial role in the control of viral replication in HIV-infected individuals. However,the virus succeeds in exploiting the immune system to its advantage and therefore, the host ultimately fails to control the virus leading to development of terminal AIDS. The virus adopts numerous evasion mechanisms to hijack the host immune system. We and others recently described the expression of inhibitory molecules on T cells as a contributing factor for suboptimal T-cell responses in HIV infection both in vitro and in vivo. The expression of these molecules that negatively impacts the normal functions of the host immune armory and the underlying signaling pathways associated with their enhanced expression need to be discussed. Targets to restrain the expression of these molecular markers of immune inhibition is likely to contribute to development of therapeutic interventions that augment the functionality of host immune cells leading to improved immune control of HIV infection. In this review, we focus on the functions of inhibitory molecules that are expressed or secreted following HIV infection such as BTLA, CTLA-4, CD160, IDO, KLRG1, LAG-3, LILRB1, PD-1, TRAIL, TIM-3, and regulatory cytokines, and highlight their significance in immune inhibition. We also highlight the ensemble of transcriptional factors such as BATF, BLIMP-1/PRDM1, FoxP3, DTX1 and molecular pathways that facilitate the recruitment and differentiation of suppressor T cells in response to HIV infection.